Penataan Wilayah pada Masa Kerajaan Sunda - Agus Aris Agus Aris (Berkala Arkeologi, 1994)
The Kingdom of Sunda is one of the kingdoms during the Hindu-Buddhist period located in West Java. Unlike the history of other kingdoms that have grown and developed on the island of Java (Mataram, Kadiri, Singhasari, Majapahit), the history of the Kingdom of Sunda is still not widely discovered by scholar. It is mainly because the historical sources related to the kingdom are very limited. There are also not too many archaeological remains. Even if the remains are visible, it is in a damaged condition. However, historians and archaeologists certainly still hope that in the future more historical sources will be found. It can help to reveal the history of the Kingdom of Sunda. This study deliberately discusses the final phase of the kingdom based on the data availability.